2002
DOI: 10.1104/pp.006072
|View full text |Cite
|
Sign up to set email alerts
|

Two Novel Mitogen-Activated Protein Signaling Components, OsMEK1 and OsMAP1, Are Involved in a Moderate Low-Temperature Signaling Pathway in Rice

Abstract: Rice (Oryza sativa) anther development is easily damaged by moderately low temperatures above 12°C. Subtractive screening of cDNA that accumulated in 12°C-treated anthers identified a cDNA clone, OsMEK1, encoding a protein with features characteristic of a mitogen-activated protein (MAP) kinase kinase. The putative OsMEK1 protein shows 92% identity to the maize (Zea mays) MEK homolog, ZmMEK1. OsMEK1 transcript levels were induced in rice anthers by 12°C treatment for 48 h. Similar OsMEK1 induction was observed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
81
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 156 publications
(98 citation statements)
references
References 55 publications
5
81
1
Order By: Relevance
“…In the same way, OsMEK1 (a putative rice MAP kinase kinase, isolated by subtractive screening of cDNA library) has been shown to interact with OsMAP1 at 12°C, suggesting that both kinases, OsMEK1 and OsMAP1, may be involved in the temperature stress signaling (Wen et al 2002). Another MAP kinase, called OsMAPK4, has also been identified in rice leaves and roots with strong upregulation by cold stress (Fu et al 2002).…”
Section: Mapks and Temperature Stressesmentioning
confidence: 89%
“…In the same way, OsMEK1 (a putative rice MAP kinase kinase, isolated by subtractive screening of cDNA library) has been shown to interact with OsMAP1 at 12°C, suggesting that both kinases, OsMEK1 and OsMAP1, may be involved in the temperature stress signaling (Wen et al 2002). Another MAP kinase, called OsMAPK4, has also been identified in rice leaves and roots with strong upregulation by cold stress (Fu et al 2002).…”
Section: Mapks and Temperature Stressesmentioning
confidence: 89%
“…Expression analysis reveals that MAPKKK OsEDR1, an ortholog of Arabidopsis AtEDR1, is probably associated with development and the defense/stress response [81]. The expression pattern of MAPK kinase OsMEK1 is similar to that of OsMAP1 under abiotic stress [178]. Both OsMEK1 and OsMAP1 messenger RNA levels are induced by treatment at a moderately low temperature (12°C) but not at 4°C.…”
Section: Mapk Pathwaymentioning
confidence: 81%
“…Two-hybrid analysis reveals that OsMEK1 interacts with OsMAP1. The OsMEK1-OsMAP1 pathway, therefore, may be involved in moderately low-temperature signaling in rice [178].…”
Section: Mapk Pathwaymentioning
confidence: 99%
See 1 more Smart Citation
“…OsMKK6 (earlier named as OsMEK1) specifically and physically interacted with OsMPK3 (earlier named as OsMAP1) in moderate low temperature stress signaling as shown by yeast two hybrid assay. 9 Transcript studies have revealed that OsMKK4 and OsMKK6 are strongly regulated by salt and cold stress.…”
mentioning
confidence: 99%